Pelatihan Penggunaan Aplikasi Reservasi Kamar Hotel Untuk Meningkatkan Layanan Konsumen - Nazori Suhandi; Rendra Gustriansyah (STMIK Royal, 2024)
The travel and tourism sectors are closely related to the hospitality sector. The success of a hotel in this digital era is strongly supported by customer service that utilizes information technology-based applications. However, using these applications effectively requires proper training and understanding. Therefore, this service activity aims to train Swarna Dwipa hotel staff in operating a web-based hotel room reservation application. It is one way for hotel staff to provide optimal service and assist in driving business success in the hospitality sector. Many studies show that operating hotel room reservation applications can increase customer satisfaction and efficiency in the hotel business. However, proper and systematic training is necessary to maintain competitiveness. The stages of this activity include observation, interviews, sharing knowledge, training in application use, and evaluation. The simulation results show that participants can use the reservation application in a structured and systematic manner with a significant level of user acceptance of applications. Keywords: application; hotel; training; reservation